Matrimonial Agreement and Validation in Court - Mariana Mariana; Benny Djaja (PT Publikasiku Academic Solution, 2023)
The purpose of the research on how a marriage agreement is applied in a legal context, including how the document is made, signed, and executed including parties outside the agreement in the event of a dispute which includes how the provisions for the division of marital property are decided after the end of the marriage, the method used is normative juridical using a descriptive analysis approach, The findings in the study are that the marriage agreement made in accordance with the applicable provisions and has been registered with the marriage registrar is valid and has also bound third parties so that when there is a dispute over marital property, it is the basis for the judge in deciding the case, marriages that have a marriage agreement do not have joint property, control of property